Effective removal of Cr(vi) from aqueous solution by biochar supported manganese sulfide. Issue 54 (2nd October 2019) - Zhang, Shiqiu; Zhang, Haiqing; Liu, Fang; Yang, Fan; Zhou, Shengnan; Zheng, Kui; Chu, Chunli; Liu, Le; Ju, Meiting
Abstract : In order to remove hexavalent chromium (Cr(vi )) efficiently and simplify the adsorbent preparation process, we employed a single step method to prepare a new biochar supported manganese sulfide material. Abstract : In order to remove hexavalent chromium (Cr(vi )) efficiently and simplify the adsorbent preparation process, we employed a single step method to prepare a new biochar supported manganese sulfide material. The nanoscale MnS particles were highly soldered on the biochar support surface, and this adsorbent displayed the effective removal of Cr(vi ) (98.15 mg L −1 ) via synergistic effect between adsorption and reduction/precipitation under weak acid conditions (pH = 5.0–6.0). The adsorption kinetic data were described well by the pseudo second-order kinetic model, suggesting that the reaction process was a chemisorption process. The adsorption isotherm data were described well by the Redlich–Peterson model, further suggesting that this reaction was a hybrid chemical reaction-sorption process. In addition, the Dubinin–Radushkevich isotherm model with 8.28, 8.57, and 12.91 kJ mol −1 adsorption energy also suggests that it was a chemisorption process. The simple and eco-friendly preparation process, low-cost, and the high removal efficiency could make it a promising material for the purification of Cr(vi )-contaminated wastewater.